2021
DOI: 10.1039/d0sc05556e
|View full text |Cite
|
Sign up to set email alerts
|

Cu-catalyzed hydroxycyclopropanol ring-opening cyclization to tetrahydrofurans and tetrahydropyrans: short total syntheses of hyperiones

Abstract: A novel Cu-catalyzed hydroxycyclopropanol ring-opening cyclization was developed to synthesize substituted tetrahydrofuran/tetrahydropyran molecules including two norlignan natural products hyperiones A and B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…J, were reported in hertz unit (Hz). 13 C NMR was recorded on 100 or 150 MHz and was fully decoupled by broad band proton decoupling. Chemical shifts were reported in ppm referenced to the center line of a triplet at 77.0 ppm of CDCl 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…J, were reported in hertz unit (Hz). 13 C NMR was recorded on 100 or 150 MHz and was fully decoupled by broad band proton decoupling. Chemical shifts were reported in ppm referenced to the center line of a triplet at 77.0 ppm of CDCl 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the broad applications of intramolecular C─O bond formation to obtain cyclic ether derivatives, many reactions often require high loading of transition metal catalysts or harsh reaction conditions such as high temperature. [7][8][9][10][11][12][13][14][15][16] In this context, the development of a mild and eco-friendly synthetic method to synthesize cyclic ether derivatives is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…However, this latter method proved to be more effective for syn-2,5-THFs, putatively due to steric strain in the transition state for the required diastereomeric substrate leading to anti-2,4 THFs (Figure 2C). 8 Given the lack of suitable methods for the construction of the key THF core of GDC-6599 (Figure 1), we sought to develop a concise synthetic sequence amenable to large-scale manufacturing. To accomplish the efficient and stereodefined synthesis of 4a, we envisioned forging the initial stereocenter by Hayashi−Heck arylation 9 of 4-chlorophenol triflate 1a and 2,3-dihydrofuran to afford 5-aryl-2,3-dihydroforun 2a (Scheme 1).…”
mentioning
confidence: 99%
“…In another example, Cuerva and co-workers showed that a Ti/Ni/Mn trimetallic system could afford anti -2,4-disubstituted THFs in good diastereoselectivity via a reductive Heck-type cyclization (Figure B). , More recently, Dai and co-workers showed that the Cu-catalyzed cyclopropyl alcohol ring opening could furnish anti -2,4 THFs. However, this latter method proved to be more effective for syn -2,5-THFs, putatively due to steric strain in the transition state for the required diastereomeric substrate leading to anti -2,4 THFs (Figure C) …”
mentioning
confidence: 99%
“…Cyclopropanols, easily accessible compounds with intrinsic strain property, are often regarded as an important class of homoenolate equivalent, which can intercept with various electrophiles to forge different functional groups at the β-position of carbonyl compounds . Pioneered by seminal works developed by Nakamura and Kuwajima using siloxycyclopropanes as the homoenolate precursor to participate in diverse addition and cross-coupling reactions mediated by metal salts, numerous ring-opening cross-coupling reactions of cyclopropanol by transition metals have been devoted to access a variety of functionalities at the β-position of ketone moiety. The existing protocols mainly focus on the intramolecular cycloisomerization or two-component cross-coupling (Scheme i, a). Despite the sustainable advances, the multicomponent reaction of the cyclopropanol is underdeveloped.…”
mentioning
confidence: 99%